Particle size (1,000 vs 500 um) affects nutritional value of simple and complex diets for weanling pigs and broiler chicks - Kim, I.H.; Cabrera, M.R.; Hines, Robert H.; Rantanen, M.M.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Nursery pigs fed complex diets had greater ADG than those fed simple diets, and as particle size was reduced, ADG and F/G tended to improve. There was a trend for reducing particle size to increase ADG more for pigs fed simple versus complex diets, but the response in efficiency of gain was of similar magnitude regardless of diet complexity. A second experiment was designed to determine if broiler chicks were an acceptable model for predicting the effects of feed processing procedures on nursery pigs. Chicks responded somewhat differently than pigs to the diet complexity x particle size treatments, with reduction of particle size having an effect only in simple diets.
Keywords: Swine; Nursery; Diet complexity; Particle size